2012
DOI: 10.3109/10837450.2012.659253
|View full text |Cite
|
Sign up to set email alerts
|

Permeability and toxicity characteristics of L-cysteine and 2-methyl-thiazolidine-4-carboxylic acid in Caco-2 cells

Abstract: Acetaldehyde is a known mutagenic substance and has been classified as a group-one carcinogen by the WHO. It is possible to bind acetaldehyde locally in the gastrointestinal (GI) tract with the semi-essential amino acid l-cysteine, which reacts covalently with acetaldehyde and forms compound 2-methyl-thiozolidine-4-carboxylic acid (MTCA). The Caco-2 cell line was used to determine the permeation of l-cysteine and MTCA, as well as the possible cell toxicity of both substances. Neither of the substances permeate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Peak MTCA concentrations of gastric juice were over 20-fold lower than MTCA levels found to be non-toxic to Caco-2 cell lines in vitro. [33] MTCA is an endogenous product that is detected in the blood after a moderate ethanol dose (0.5 g/kg). [34] Furthermore, it has been shown that MTCA can serve as a prodrug for L-cysteine and thus protect mice against acetaminophen toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Peak MTCA concentrations of gastric juice were over 20-fold lower than MTCA levels found to be non-toxic to Caco-2 cell lines in vitro. [33] MTCA is an endogenous product that is detected in the blood after a moderate ethanol dose (0.5 g/kg). [34] Furthermore, it has been shown that MTCA can serve as a prodrug for L-cysteine and thus protect mice against acetaminophen toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…1). 9,10,27 Treatment of HEK293T cells with HCHO or AcH led to increased thioproline and MTCA levels, respectively (Fig. 1b).…”
Section: Aldehydes Decrease Cellular Asparagine Levels By Regulating ...mentioning
confidence: 93%
“…In cytotoxicity assays, Kartal-Hodzic et al showed that L-cysteine was not toxic to the Caco-2 cells until a concentration of 9.9 mM was reached. The results of this toxicity study are very interesting because it demonstrated that L-cysteine might be able to be used in different formulations [22]. Previously, was reported that L-cysteine and L-cystine greatly potentiated the bactericidal effect of hydrogen peroxide in E. coli K-12 [23].…”
Section: Determination Of Ros By the Chemiluminescence (Cl) Assaymentioning
confidence: 93%